2011
DOI: 10.1128/jb.01037-10
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Lpt Machinery for Lipopolysaccharide Transport to the Cell Surface: LptA-LptC Interaction and LptA Stability as Sensors of a Properly Assembled Transenvelope Complex

Abstract: Lipopolysaccharide (LPS) is a major glycolipid present in the outer membrane (OM) of Gram-negative bacteria. The peculiar permeability barrier of the OM is due to the presence of LPS at the outer leaflet of this membrane that prevents many toxic compounds from entering the cell. In Escherichia coli LPS synthesized inside the cell is first translocated over the inner membrane (IM) by the essential MsbA flippase; then, seven essential Lpt proteins located in the IM (LptBCDF), in the periplasm (LptA), and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
117
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(133 citation statements)
references
References 43 publications
15
117
1
Order By: Relevance
“…The Tn5 insertion in the RSc0411 mutant is projected to result in a truncated RSc0411 protein (Fig. S1) similar to a non-functional truncated protein of E. coli LptC that is highly unstable and fails to interact with LptA, leading to LptA destabilization and impaired LPS transport (Sperandeo et al, 2011). Our results demonstrate that RSc0411 mutation is responsible for various LPS-related defects of the mutant, including increased membrane permeability, reduced level of R-LPS production, biofilm formation and root attachment.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The Tn5 insertion in the RSc0411 mutant is projected to result in a truncated RSc0411 protein (Fig. S1) similar to a non-functional truncated protein of E. coli LptC that is highly unstable and fails to interact with LptA, leading to LptA destabilization and impaired LPS transport (Sperandeo et al, 2011). Our results demonstrate that RSc0411 mutation is responsible for various LPS-related defects of the mutant, including increased membrane permeability, reduced level of R-LPS production, biofilm formation and root attachment.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, previously Sperandeo et al (2011) proposed that LptA binds to the C-terminal region of LptC. They showed that a mutated form of LptC (LptCG153R) conferred reduced affinity to LptA and that a truncated LptC (LptC177-191), lacking the second disordered region at the C-terminal region (Fig.…”
Section: Specificity In Duf1239 Proteins Interactions With Their Intementioning
confidence: 99%
See 2 more Smart Citations
“…1A). LptB/F/G form an ABC transporter that is believed to extract LPS from the IM (18)(19)(20); LptC associates with LptB/F/G and periplasmic LptA (21,22); and LptD/E form a complex at the OM (23)(24)(25). All Lpt factors are required for LPS transport and viability in E. coli (19,20,24,26), and they form a transenvelope protein bridge that is thought to mediate transport of LPS from the IM to the OM (27,28).…”
mentioning
confidence: 99%